Influence of cold work and plate thickness on the gas-tungsten arc weldability of commercially pure aluminium - Karaaslan, Ahmet (CARL HANSER VERLAG, 2006)
This body of work reveals the weldability of commercially pure aluminium after the base metal received different amounts of hot and cold work. This process included the continuous casting of molten aluminium Alloy 1235 directly into an endless coiled strip suitable for cold rolling. Following casting and hot rolling, the material was cold rolled (at room temperature) to different thicknesses and reduction ratios. Gas-tungsten arc welding (GTAW) was used to join the aluminium plats after both hot and cold rolling operations. The purpose of these studies was to determine the influence of the workpiece temper condition and thickness on weldability. This contribution summarises the main results of this investigation.
Keywords: Materials Science